Traveltime delay and initial phase reversal of distant tsunamis coupled with the self‐gravitating elastic Earth. Issue 5 (15th May 2014) - Watada, Shingo; Kusumoto, Satoshi; Satake, Kenji
Abstract: Systematic tsunami traveltime delays of up to 15 min relative to the numerically simulated long waves from the 2010 Chilean and 2011 Tohoku‐Oki earthquakes were widely observed at deep ocean tsunamimeters. Enigmatic small negative phases appearing before the main peak were commonly found only at the trans‐oceanic locations. The frequency dependence of the measured tsunami phase velocities shows reverse dispersions at long periods, i.e., the tsunami speed becomes slower at periods beyond 1000 s. This is consistent with the phase velocities of a tsunami mode coupled with a self‐gravitating elastic Earth, suggesting that the effects of compression and dilatation of seawater, elastic tsunami loadings on a solid Earth, and the geopotential variations associated with the motion of mass during tsunami propagation are responsible for the traveltime delays and the initial negative phases. Simple 1‐D tsunami propagation tests confirm that the reverse dispersion creates a small negative phase that precedes the main peak at large distances. A new method to simulate tsunami waveforms on real ocean bathymetry that takes into account seawater compressibility, the elasticity of the Earth, and geopotential perturbations has been developed by applying a phase correction to the simulated long waves. The simulated waveforms, in which phase corrections are applied for the dispersion effects, accurately reproduce the observed waveforms, including a small initial negative phase that appears at distant locations. The traveltime difference between the observed and simulated waveforms has been decreased to less than 5 min and the waveform difference between them remarkably diminishes. Key Points: Traveltime delay and wave dispersion of a trans‐oceanic tsunami were detected They are reproduced by a tsunami model coupled with gravitating elastic Earth Phase‐corrected synthetic tsunamis accurately simulate the observed waveforms